QUARTER OF A CENTURY IN THE LOOKING FOR OPTIMAL WAYS TO PREVENT NONINFECTIOUS DISEASES AND NEW TASKS FUTURE (TO THE 25TH ANNIVERSARY OF THE STATE RESEARCH CENTER FOR PREVENTIVE MEDICINE FOUNDING) (Рациональная фармакотерапия в кардиологии)
.